PENINGKATAN PARTISIPASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH DI MASA PANDEMI - Tiarima Marbun (Khazanah Pendidikan, 2021)
This classroom action research (CAR) was conducted to increase student success in learning History with the Google Classroom (GC) application. The class as the subject is that of XI IPS-2 SMA Negeri 2 Tarakan, consisting of 36 students, with 19 male and 17 female students. They were chosen,  because the class saw a very large level of online learning problems such as: students often missed class, attended late, did not do assignments, did not have data packages so they did not participate in learning , and very passive learning activities.This research was conducted in two cycles, with  three meetings in each. It employed GC as the media to hold the learning process done online in the pandemic era. The results of the analysis has proved that the use of GC can help in improving student learning outcomes, based on all aspects of observation and action so that learning outcomes increase in each meeting and cycle. The learning outcomes in the first cycle showed 47.2%, while in the second cycle it increased to 83.3%. There were 5 students or 13.9% who had failed to reach the minimum completeness and a student was not present at the last meeting of the cycles. A remedial will be given in a separate meeting so that they can achieve the required mastery in learning. In short, learning with GC media can improve the results of learning history subject for the students in high school. Therefore, it is recommended that teachers or teachers be able to use GC in online learning.